(untitled) (Colombia Medica, 2008)
Introduction: Keratoconos is a cornea disorder that affects young people and is a contraindication for refractive surgery; it could be treated with contact lens, corneal transplantation or with intracorneal ring segments (Intacs) insertion. Purpose: To compare mean power keratometric maps and posterior elevation maps in delineating keratoconus characteristics and guide Intacs implantation. Methods: 23 eyes with keratoconus, 12 subjects, cone area, cone radii, cone peak area and coordinates were measured using both maps and were compared using t test. Statistical significance was defined as p< 0.05. Correlations were assessed with Pearson’s coefficient. Results: Mean cone area was 17.65 mm² ± 4.63 and 35.68 mm² ± 9.72 in posterior elevation map and mean power keratometric analysis respectively (p 0.00). Both posterior elevation and mean power keratometric maps finds a similar percentage split between centre cones (CC) and de-centered cones (DC) of 78:22. However, 9% cases were found not to match after case to case evaluation. Conclusion: Based on the cases that not matched the cone centration, we suggest a new way to define the cone centre using the mean power keratometric map. Therefore, it should be review the decisions to implant symmetric rings vs. asymmetric rings using posterior elevation map. A new parameter is discussed «cone peak centration» in de-centered cones (DC).